2016
DOI: 10.1007/s10787-016-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid ameliorates chronic constriction injury induced painful neuropathy in rats

Abstract: In conclusion, the anti-hyperalgesic effect of FA in rats receiving CCI might partly be attributed to its anti-oxidant and anti-inflammatory activity and is associated with the maintenance of neuropathic pain and could be useful as an adjuvant to conventional medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
12
1
1
Order By: Relevance
“… 39 Previous reports refer to antinociceptive action of ferulic acid (monomer, FAM) through the opioid pathway, as it has shown positive results in neurogenic pain models. 30 , 39 In the current study, FAM did not suppress acute pain in male mice although it was as potent as FAD in alleviating late-phase pain in female mice. Several reports have suggested that there is a clear sex difference in pain perception and pain inhibition in both human and mouse models.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“… 39 Previous reports refer to antinociceptive action of ferulic acid (monomer, FAM) through the opioid pathway, as it has shown positive results in neurogenic pain models. 30 , 39 In the current study, FAM did not suppress acute pain in male mice although it was as potent as FAD in alleviating late-phase pain in female mice. Several reports have suggested that there is a clear sex difference in pain perception and pain inhibition in both human and mouse models.…”
Section: Discussioncontrasting
confidence: 43%
“… 8 As indicated earlier, FAM has been shown to suppress neurogenic pain via opioid receptor action. 30 , 39 With the experiments performed so far, we believe that FAD does not work through the opioid pathway as it suppresses only inflammatory response in formalin model and did not show any apparent neurogenic locomotor impairment, and opioid antagonist did not reverse its antinociceptive effect. In addition, mechanical hyperalgesia and thermal sensitivity tests indicate that normal nociception was retained in mice after FAD treatment, which suggests that neurologic functions are maintained.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[16]; dose-dependent amelioration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced loss of nigrostriatal dopaminergic neurons, the decrease of the Bax/Bcl2 ratio, reduction of pro-apoptotic protein Bax levels and increased expression of anti-apoptotic protein Bcl2 in PD C57BI/6 mice model (ferulic acid was given via injections for 7 days, at a dose of 20, 40 and 80 mg/kg) [17];…”
Section: Figurementioning
confidence: 99%
“…In the present study an attempt was made to explore the potential effects of naturally isolated ECN in PSNL-induced model of neuropathic pain. PSNL model has been used clinically for the treatment of neuropathic pain [25]. Intraperitoneal administration of ECN (10 mg/kg) post-treatment once daily starting from day 3 after surgery, significantly attenuated mechanical hyperalgesia, thermal hyperalgesia, mechanical allodynia and cold allodynia.…”
Section: Discussionmentioning
confidence: 99%